2018
DOI: 10.1016/j.jped.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and musculoskeletal syndromes in adolescents are related to electronic devices

Abstract: A high prevalence of musculoskeletal pain/syndromes was observed in female adolescents. Musculoskeletal pain was mostly reported at a median age of 15 years, and students used at least two electronic devices. Reduced use of electronic games was associated with musculoskeletal pain syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
12

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 24 publications
0
23
1
12
Order By: Relevance
“…Students typically spend many hours seated on non-ergonomic chairs and assuming incorrect postures to carry out their curricular activities, leading to a general musculoskeletal overload [5]. Furthermore, while spending much time using laptops and smartphones to study and support leisure activities, they adopt incorrect postures, leading to musculoskeletal alteration and pain, especially to the neck and the spine [6]. Haroon et al [7] reported a high incidence of MP in Karachi's university medical students, identifying the usage of laptops for more than three hours per day as a risk factor for neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…Students typically spend many hours seated on non-ergonomic chairs and assuming incorrect postures to carry out their curricular activities, leading to a general musculoskeletal overload [5]. Furthermore, while spending much time using laptops and smartphones to study and support leisure activities, they adopt incorrect postures, leading to musculoskeletal alteration and pain, especially to the neck and the spine [6]. Haroon et al [7] reported a high incidence of MP in Karachi's university medical students, identifying the usage of laptops for more than three hours per day as a risk factor for neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic myofascial pain is common in the paediatric population and its prevalence has increased since the 1980s [139]. Musculoskeletal pain is a common cause of pain in adolescents, with incidence ranging from 30 to 65% [140][141][142][143][144], and is a leading cause of years lived with disability among children and adolescents [145]; 4% of all primary care consults represent musculoskeletal issues in children aged up to 15. Between 4 and 40% of adolescents report limb pain and 14-24% complain of Near indwelling mesh to minimise risk of infection.…”
Section: Case Based Discussion Of Important Pointsmentioning
confidence: 99%
“…A principal hipótese é de que as mulheres se queixam mais e referem mais dor do que os homens, especialmente quando se trata de síndromes musculoesqueléticas amplificadas, e que isso pode ter relação com aspectos socioculturais. 2,3,6 .…”
Section: Resultados ________________________________________________________ 6-resultadosunclassified
“…A dor musculoesquelética foi acentuada em adolescentes do sexo feminino, conforme descrito em outros estudos 2,3,[5][6][7]12,14,35 Além disso, o questionário possui uma grande confiabilidade confirmada no teste-reteste para essa população, apontando uma real concordância entre as respostas do pré-teste e do reteste em um intervalo de cerca de trinta dias, como também foi demonstrado em outras publicações 2,3,5,6 .…”
Section: Resultados ________________________________________________________ 6-resultadosunclassified
See 1 more Smart Citation